Vortex shedding from a wind turbine blade section at high angles of attack - MESKELL, CRAIG (My University, 2013)
The unsteady flow around a stationary two-dimensional wind turbine blade section (NREL S809) has been simulated using unsteady RANS with the SST turbulence model at Re = 106 and high angles of attack. Vortex shedding frequency non-dimensionalised by the projected area of the blade is in the range 0.11 < St < 0.16. The fluctuating coefficients at the harmonics of the fundamental vortex shedding frequency for lift, drag and pitching moment are presented. The lift force and the pitching moment (calculated with respect to the midchord) are dominated by the fundamental vortex shedding frequency, but significant contributions at the higher harmonics are also present. For the drag the second harmonic is as significant as the fundamental frequency, with the third and fourth harmonics contributing to a lesser extent. From the results, it is inferred that the camber of the airfoil does not substantially affect the force coefficients, suggesting that the results presented may be generally applicable to turbine blades of different geometry.
PUBLISHED
Keywords: wind turbine; vortex shedding